Rancang Bangun Pendingin Ruang Otomatis Menggunakan Mikrokontroler dan Sensor Pir - Ramadhan, Muhammad Rama; Wijaya, Ryan Aji; Firdhayanti, Ayu (LPPM Universitas Muhammadiyah Kotabumi, 2024)
Various industries have been impacted by advances in automation technology, such as energy management and temperature control in enclosed spaces. One interesting application is an automated air conditioning system, which aims to reduce energy wastage in the use of conventional chillers. Inefficient use of air conditioners often leads to high carbon emissions and energy wastage, especially in tropical countries like Indonesia. To improve the efficiency of the cooling system, you can use passive infrared (PIR) sensors. Activated only when people are present in the room, PIR sensors detect changes in the radiation produced by the human body. PIR sensors can be connected to cooling systems with microcontrollers such as Arduino and ESP8266. This enables automatic remote control and monitoring. The purpose of this research is to create and implement a PIR sensor-based automatic air conditioning system equipped with an Arduino controller. Evaluation is conducted to test the performance of the system in detecting human presence and controlling the air conditioner automatically. It is expected that this system will be a simple and efficient solution to reduce the energy usage of conventional air conditioners. In addition, it will support energy efficiency and environmental sustainability.